COMPARATIVE PRECISION OF THE PIVOTAL ESTIMATORS OF PARTICLE SIZE - Luis M Cruz-Orive (Image Analysis and Stereology, 2011)
The pivotal estimators of the surface area and the volume of a generic "particle" are based on a point sampled test line on an isotropic pivotal plane through a fixed point called the pivotal point. The purpose of this paper is to compare the precision of the pivotal estimator of surface area against the surfactor on the one hand, and of the pivotal estimator of volume against the nucleator on the other. For the sake of a tractable but informative model we compute exact variances for a spherical particle with an eccentric nucleolus.